BLACK LIVES MATTER IN THE UNITED STATES - Alifianita Amalia; Luthfiyah Alifah Ridwan; Rachel Krisna Ayu; Shuwen Lian (Sociae Polites, 2021)
This paper examines affiliation with the Black Lives Matter (BLM) movement using the constructivism theory. The main finding presented in the paper is that the discrimination experienced by African Americans in the United States in the past two decades. The BLM movement's history was a response to the death of two black teenagers, Trayvon Martin and Michael Brown, who were both unarmed and shot and killed. The most famous one happened this year, the death of George Floyd for the brutal police action by pressing the victim's neck with his leg until Floyd died. The second key finding is that BLM organizations generated more to frame the movement as a struggle for individual rights. Still, many youths assume that this movement is just a trend on social media. Finally, social media's influence where the spread of news, content, videos is the important point of the black lives matter movement in the US.